Rekonsepsi Amicable Divorce (Cerai-Damai) Berbasis Paradigma Mubadalah: Upaya Mewujudkan Keadilan Gender dalam Hukum Perceraian Indonesia - Maliki, Ibnu Akbar; Aimar, Qeis; Badarudin (Institut Agama Islam Negeri Metro, 2025)
Abstract: This research stems from the concern over the persistent gender bias in the construction of divorce law in Indonesia, as stipulated in Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). The legal norms that position the husband as the primary holder of the right to divorce (talak) and the wife as the passive party reflect relational inequality, which leads to social and legal injustice. Through a normative juridical approach with the mubadalah paradigm which emphasizes the principles of reciprocity and relational justice this study seeks to reconceptualize divorce law toward a gender-just model of amicable divorce. The findings reveal that the mubadalah paradigm can serve as an ethical and theoretical foundation for shifting the orientation of divorce law from a power-based relationship to one of mutuality, where divorce is understood as a joint process aimed at preserving the well-being and dignity of both parties. This study recommends reforming Islamic family law through amendments to the Marriage Law and the KHI, strengthening equality-based mediation institutions, and enhancing institutional capacity and public education from a gender perspective. Thus, amicable divorce based on mubadalah becomes not only a conceptual proposal but also a practical strategy toward a more just, humanistic, and compassionate Islamic family law in line with the spirit of rahmatan lil ‘alamin. Keywords: Amicable Divorce, Mubadalah, Gender Justice, Islamic Family Law, Divorce Law.